Hubungan Kecerdasan Spiritual dengan Kemampuan Membaca Al-Qurâ€™an Mahasiswa Prodi PAI IAIN Surakarta Tahun 2018 - Zulfa Wahda Anindita; Retno Wahyuningsih (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2021)
The background of this research was there were still islamic education students (PAI) whose thesis exams were postponed because their reading capability of the Qur'an is not good and there were gaps in theory and reality that students with high spiritual intelligence, their ability to read the Qur'an is not good enough. The purpose of this study was to determineÂ the spiritual intelligence,the ability to read the Al-Qur'anandthe relationship between Spiritual Intelligence and the Ability to Read the Koran in the 2018 Islamic Education Study Program,Faculty of Education IAIN Surakarta. Theresearch used Proportionate Random Sampling technique. The test normality of spiritual intelligence using the Liliefors test, and hypothesis testing using the product moment correlation test. The results of this study showed that: The spiritual intelligence of PAI students of 2018 FIT IAIN Surakarta was categorized as high; The ability to read the Al-Qur'an students of the PAI class 2018 FIT IAIN Surakarta is categorized as high; The results of hypothesis testing obtained r count (0.0307671) <r table (0.1697) at the 5% significance level. This means that there is no relationship between spiritual intelligence and the ability to read the Koran in the 2018 Islamic Education Study Program.